Topological polaritons and excitons in garden-variety systems - Bardyn, Charles-Edouard (2015)
We present a practical scheme for creating topological polaritons in garden-variety systems based, for example, on zinc-blende semiconductor quantum wells. Our proposal requires a moderate magnetic field and a potential landscape which can be implemented, e.g., via surface acoustic waves or patterning. We identify indirect excitons in double quantum wells as an appealing alternative for topological states in exciton-based systems. Topological polaritons and indirect excitons open a new frontier for topological states in solid-state systems, which can be directly probed and manipulated while offering a system with nonlinear interactions.